How the West was won - Baker, Carroll, 1931-; Cobb, Lee J., 1911-1976.; Fonda, Henry, 1905-1982.; Ford, John, 1894-1973.; Tracy, Spencer, 1900-1967.; Marshall, George, 1891-1975.; Hathaway, Henry, 1898-1985.; Metro-Goldwyn-Mayer.; Cinerama Releasing Corp. (Burbank, CA : Warner Home Video, 1999)
An all-star cast and three directors present an epic film about the American movement westward, focusing on the life of one family and its dreams of land, gold, and glory.
Disc label title.
Widescreen version.
Originally released as a motion picture in 1962.
Special features: behind-the-scenes documentary The making of How the west was won, interactive menus, scene access.
Director of photography, William Daniels ... [et al.]; art director, George Davis ... [et al.]; editor, Harold F. Kress.; narrator, Spencer Tracy; music, Alfred Newman.
Carroll Baker, Lee J. Cobb, Henry Fonda, Carolyn Jones, Karl Malden, Gregory Peck, George Peppard, Robert Preston, Debbie Reynolds, James Stewart.
Keywords: Historical films; Action and adventure films; West (U.S.) -- Discovery and exploration -- Fiction; Feature films